To solve the equation \( 2x - 5 = 3(4x + 5) \), the steps can be ordered as follows:
-
Step 1: Distributive - First, distribute the \(3\) on the right side of the equation:
\[ 2x - 5 = 12x + 15 \] -
Step 2: Subtraction of Equality - Next, subtract \(12x\) from both sides:
\[ 2x - 12x - 5 = 15 \]
This simplifies to:
\[ -10x - 5 = 15 \] -
Step 3: Addition of Equality - Then, add \(5\) to both sides:
\[ -10x = 20 \] -
Step 4: Division of Equality - Finally, divide both sides by \(-10\):
\[ x = -2 \]
So, the correct order of the steps for solving the equation is:
- Step 1: Distributive
- Step 2: Subtraction of Equality
- Step 3: Addition of Equality
- Step 4: Division of Equality